Synodality and the Sacramental Mission of the Church: The Struggle for Communion in a World Divided by Colonialism and Neoliberal Globalization. (March 2022) - Miller, Vincent J.
This article examines an aspect of synodality that remains under-theorized: the expansion of listening and discernment beyond the church to the entire human community, facilitating attention to the "cries of the poor and the earth" that has the potential to engender forms of communication that current global structures neither facilitate nor allow. Synodality entails a struggle not only against ad intra obstacles such as clericalism and centralization but also against the relationship-constructing power of colonialism and neoliberalism. In this way, Pope Francis's call for a "synodal Church" can be understood as developing the sacramental character of the church articulated in Lumen Gentium .